2020
DOI: 10.1177/2633366x20922856
|View full text |Cite
|
Sign up to set email alerts
|

Functionally graded wood filler–recycled polypropylene composite: Effect of mechanical loading on deflection of cantilever beam

Abstract: Structures made from natural fiber–polypropylene composite material usually have uniform mechanical properties throughout. In some applications, such as in products with snap-fit assembly, it is desirable to have lower stiffness in some parts of the structure while having significantly higher stiffness at other parts of the same structure. In this research, the effect of changing the material arrangement and composition in a cantilever beam made from functionally graded natural filler–recycled polypropylene (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…By placing the wood sawdust in specific areas, material with disparate stiffness in its sections can be achieved. At this point it is expected that this kind of material could be used in snap fit parts in connections or quick release parts [38]. This kind of parts could be used in products compliant with eco-design principles [39] replacing polypropylene with biodegradable plastic like polylactic acid.…”
Section: Materials From Wood Residuesmentioning
confidence: 99%
“…By placing the wood sawdust in specific areas, material with disparate stiffness in its sections can be achieved. At this point it is expected that this kind of material could be used in snap fit parts in connections or quick release parts [38]. This kind of parts could be used in products compliant with eco-design principles [39] replacing polypropylene with biodegradable plastic like polylactic acid.…”
Section: Materials From Wood Residuesmentioning
confidence: 99%
“…The impact strength of the recycled composites increased by 23.3% under 30.0 wt% fly ash. Bahri et al [9] fabricated functionally graded natural filler-recycled polypropylene (FGNF-RPP) composite and investigated deflection behaviour under static mechanical loads. The results showed that composite under 40.0 wt% waste wood sawdust produced the least deflection.…”
Section: Introductionmentioning
confidence: 99%
“…The impact strength of the recycled composites increased by 23.3% under 30 wt % fly ash. Bahri et al 5 fabricated a functionally graded natural filler-recycled polypropylene (FGNF-RPP) composite and investigated deflection behavior under static mechanical loads. The results showed that the composite under 40% waste wood sawdust produced the least deflection.…”
Section: Introductionmentioning
confidence: 99%